Sickle cell disease: suspect, check, diagnose—practical tips for non-SCD experts to suspect and diagnose SCD in low-prevalence European settings - Palazzi, Giovanni; Benemei, Silvia; Gallucci, Cristiano; Arcioni, Francesco; Perrotta, Silverio (Frontiers in Medicine, 2025)
Sickle cell disease (SCD) is the most common monogenic disorder, including a group of autosomal recessive hemoglobinopathies characterized by hemoglobin polymerization and sickling of red blood cells when low oxygen concentrations are present. SCD has a growing public health significance, affecting nearly 8 million people globally, with a high prevalence observed in Sub-Saharan Africa and Mediterranean countries. Improved understanding of SCD is essential, particularly given recent migratory flows that have contributed to an increase in the number of affected individuals in Europe and Italy. An early diagnosis is crucial to start the appropriate therapy to ensure the patients with the best outcome and improved quality of life, but clinical signs of SCD are often not easily recognized as symptoms are nonspecific and difficult to frame within the context of a congenital hemolytic disease. Given the availability of simple and multiple diagnostic tools, a simplified approach based on red-flags can facilitate the diagnostic suspicion in clinical practice to promptly identify individuals to be referred to specialized centers. The present narrative review aims to discuss the main clinical features, diagnostic tools of SCD, and provide practical illness scripts to facilitate the approach of non SCD-expert healthcare professionals to its diagnosis. Patient’s history, including ethnicity, region of origin, familial cases of SCD and other congenital or unexplained anemias, previous clinical manifestations, remain fundamental in guiding diagnostic suspicion of SCD, together with a few crucial lab parameters. The implementation of screening projects is essential to ensure early diagnosis and rapid access to care for affected individuals.